Pasang Naik Dan Surut Kota-Kota Pantai Utara Jawa, Sebuah Model Kajian - nfn. Nurhadi (Balai Arkeologi Yogyakarta, 1995)
This presentation is based on a structural functionalistic framework; The city is tried to be seen from two sides, internal structure and external function. These two sides are a systemic unity, in the sense that changes or the inadequacy of one side will affect the other in the growth and sustainability of the city. As a group of masses that is large enough in a micro-city, it is a very complex socio-political organization, which means that a massive urban society is actually formed from a number of different and layered human agglomerates. This difference is due to cultural sentiments, that urban people place themselves in similarities and differences between one another. Meanwhile, the coating is determined on the level of authority in obtaining material, information and rights in determining and making decisions on others.